Lectotypification of three names in Cicer (Fabaceae) - Krivenko, Denis; Tatanov, Ivan (Phytotaxa, 2021)
Cicer Linnaeus (1753: 738), as currently established, includes about 50 species distributed from north to south from the Altai Mountains (C Asia) to the East African Rift (E Africa), and from west to east from the Canary Islands (W Africa) to the upper Irtysh River in Dzungaria (C Asia) (van der Maesen et al. 2007, Dönmez 2011, Toker et al. 2021). In the course of our revisionary work on this genus for Caucasian flora conspectus (Takhtajan 2003), we found the name C. anatolicum Alefeld (1861: 349) and its synonym C. glutinosum Alefeld (1861: 349), also the name C. minutum Boiss. & Hohen. in Boissier (1849: 130) that warrant lectotypification in accordance with the Shenzhen Code (Turland et al. 2018). The second-step lectotypification is made for C. anatolicum and C. minutum, while the lectotype is selected for C. glutinosum based on the analysis of their protologues and original herbarium material deposited in C, BM, G, LE, M, MO, P and WAG. Herbarium acronyms mentioned here follow Thiers (2021-onward).